A 0.3 V Current Differencing Buffered Amplifier and Its Application in Current-Mode Third-Order Low-Pass Filters - Fabian Khateb; Montree Kumngern; Tomasz Kulej (Applied Sciences)
This paper introduces an innovative low-voltage, low-power current differencing buffered amplifier (CDBA). The proposed CDBA utilizes a bulk-driven MOS transistor operating in the subthreshold region, allowing it to function effectively at low supply voltages while minimizing power consumption, making it suitable for sensor and biomedical applications. To demonstrate the performance of the proposed CDBA, it is incorporated into the design of a current-mode, third-order low-pass filter that is specifically tailored for bio-sensing applications. Both the CDBA and the low-pass filter are designed and simulated in Cadence Virtuoso using the TSMC 0.18 µm CMOS process. The CDBA operates at a supply voltage of 0.3 V, consuming 170 nW of power, while the third-order low-pass filter achieves a dynamic range of 57.2 dB with a total harmonic distortion (THD) of 1%.